Hubungan antara Kepercayaan dan Keterpaparan Informasi dengan Pengetahuan dan Sikap terhadap Perawatan Metode Kanguru pada Bidan di Kabupaten Musi Rawas Sumatera Selatan Tahun 2016 - Mudiyah, Siti; Pratomo, Hadi; Besral, Besral (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2016)
Background: Infant and Neonatal mortality in Musi Rawas District is the highest in Southern Sumatera in 2014. Implementation of kangaroo mother care as Low Birth Weight treatment is still limited in the provincial general hospital Dr. Mohammad Hoesin, Palembang. At the present time, midwives as maternal and child health service provider, can access many information including Kangaroo Mother Care from various media.Objectives: This study aimed to analyze the relationship between belief in the myth of LBW care and exposure information with the knowledge and attitudes toward kangaroo mother care on midwives in Musi Rawas District of Southern Sumatra 2016.Method: Cross sectional study design used on 197 midwives with purposive sampling.Result and Discussion: The results showed that midwives who have relatifely good knowledge about KMC As much as 50,8% and having relatively positive attitude towards KMC as much as 40.1%. There are a significant relationship between belief of LBW care (Ï=0,001; OR: 3,1; 95% CI: 1,6 â€“ 5,8), exposure information from scientific media (Ï=0,039; OR: 2,4; 95% CI: 1,0 â€“ 5,4), training (Ï=0,001; OR: 3.5; 95% CI: 1.7 â€“ 7,5) with knowledge about KMC on midwives.Conclusion: A significant relationship also demonstrated between exposure information from training with attitude towards KMC on midwives (Ï=0,003; OR: 2,8; 95% CI: 1,4 â€“ 5,6). Improving quality of the midwives in Kangaroo Mother Care is very important so midwives can provide counseling, information, and education to mother since detected with LBW.Keywords: Kangaroo Mother Care, Midwife, Belief, Attitude, Knowledge of KMC